KEEFEKTIFAN MEDIA PERMAINAN EXSYS QUARTET UNTUK MENINGKATKAN KETERAMPILAN BERKOMUNIKASI SISWA PADA MATERI SISTEM EKSKRESI MANUSIA - Alifia Suryatin Ramadani; Mohammad Budiyanto (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
communication skills on the material of the human excretion system. The type of research refers to the One Group Pretest Posttest Design research design. The subjects in this study were 16 VIII A students at Al Falah Ketintang Junior High School. The results of the feasibility of the game media based on effectiveness can be seen from the n-gain scores obtained and achievements on each indicator. There are 5 indicators used in measuring communication skills. The indicator expresses an opinion and answers the question logically with the right concept has an n gain score of 0.85, the indicator expresses an opinion with a good choice of words and has an n gain score of 1.00, the indicator expresses an opinion and answers questions using sound articulation a good one has an n gain score of 0.89, indicators express opinions and answer questions using good body gestures have n gain scores of 0.67, and indicators express opinions and answer questions smoothly and confidently have n gain scores of 0.75. The average indicator improvement of students' communication skills on natural science subjects in the human excretion system is 0.83 with high criteria. The conclusion of this research is the exsys quartet game media to practice communication skills on the material of the human excretion system, which is feasible to use in the learning process from the aspect of effectiveness